Kinetic Modifications of C4 PEPC Are Qualitatively Convergent, but Larger in Panicum Than in Flaveria - Moody, Nicholas R.; Christin, Pascal-Antoine; Reid, James D. (Frontiers in Plant Science, 2020)
C4 photosynthesis results from a set of anatomical features and biochemical components that act together to concentrate CO2 within the leaf and boost productivity. This complex trait evolved independently many times, resulting in various realizations of the phenotype, but in all C4 plants the primary fixation of atmospheric carbon is catalysed by phosphoenolpyruvate carboxylase. Comparisons of C4 and non-C4 PEPC from a few closely related species suggested that the enzyme was modified to meet the demands of the C4 cycle. However, very few C4 groups have been investigated, hampering general conclusions. To test the hypothesis that distant C4 lineages underwent convergent biochemical changes, we compare the kinetic variation between C4 and non-C4 PEPC from a previously assessed young lineage with those from an older lineage found within the distantly related grass family. Despite the evolutionary distance, the kinetic changes between the non-C4 and C4 PEPC are qualitatively similar, with a decrease in sensitivity for inhibitors, an increased specificity (kcat/Km) for bicarbonate, and a decreased specificity (kcat/Km) for PEP. The differences are more pronounced in the older lineage, suggesting that optimization of PEPC for the C4 context continues after the initial origin of the trait and increases with evolutionary time.